Challenges Faced by Widows in Khotang, Nepal: An Exploration through Bourdieu’s Theory of Capital - Rai, Puspa Raj Rai; Acharya, Chiranjibi; Nakarmi, Sudeep Singh (Molung Educational Frontier, 2026)
This article explores the multifaceted challenges faced by widows through the lens of Pierre Bourdieu’s theory of capital. The explorative and descriptive research design has been applied in this study. Primary data were collected using an interview schedule, and secondary data were collected from various websites and libraries. The study shows that widows have significantly reduced their economic capital, experienced food insecurity, faced systemic difficulties in employment, and had difficulty earning sustainable livelihoods due to a lack of access to credit. Social capital is precarious, and they do not participate in family support and community activities. Cultural capital is limited, as widows lack legal awareness, and low education levels restrict empowerment. Traditional gender norms persist. This article argues that structural inequalities perpetuate the marginalization of widows. So, intensive research will be needed on the widow’s situation, applying cross-causation of three capitals like economic capital, social capital, and cultural capital.